Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/pr11030700
|View full text |Cite
|
Sign up to set email alerts
|

Drying Kinetics, Physicochemical and Thermal Analysis of Onion Puree Dried Using a Refractance Window Dryer

Abstract: Onions have a high moisture content, which makes them more susceptible to microbial growth. Drying is one of the postharvest preservation methods applied to decrease onion moisture content, thereby increasing its storage life. In this study, onions were peeled, washed, cut into quarters, hot water blanched, and pureed. The puree was further dried using two different drying methods: refractance window drying (RWD) (water temperature: 70 °C) and convective drying (CD) (50 °C). The puree was spread on prefabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Compared to conventional methods such as convective and freezedrying, RW drying boasts shorter processing times and higher energy efficiency [19,22,23]. The refractance window technique has demonstrated success in processing a diverse range of biomaterials, including tomatoes [22], strawberries [24], carrots [24], mangoes [25], açaí [26], guavas [27], passion fruit [28], bananas [29], onion [30], apples [31], and even unconventional items like yogurt [32] and microalgae [33].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional methods such as convective and freezedrying, RW drying boasts shorter processing times and higher energy efficiency [19,22,23]. The refractance window technique has demonstrated success in processing a diverse range of biomaterials, including tomatoes [22], strawberries [24], carrots [24], mangoes [25], açaí [26], guavas [27], passion fruit [28], bananas [29], onion [30], apples [31], and even unconventional items like yogurt [32] and microalgae [33].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, recent research has focused on proposing solutions based on the use of artificial vision and machine learning to solve this type of problem [3]. Through the use of artificial intelligence, such as the implementation of artificial neural networks, it has been possible to evaluate complex systems for the prediction and control of different areas in the food industry, such as extrusion [4], process conditions (formulations) [5], drying [6], or evaluating its functional content [7]. In the last few years, artificial neural networks have proven to be advantageous because they allow the evaluation of complex and multivariable systems, thus providing an indicator that demonstrates the quality of a product.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research efforts have been directed towards investigating the drying characteristics of various fruits and vegetables, mostly concerning process parameters and the development of mathematical models. For instance, Zalpouri et al (2023) reported the drying of onion (Allium cepa L. 'Punjab Naroya') puree using two different drying methods (refractance window drying and convective drying). It was observed that irrespective of the drying method, the moisture ratio decreased, and drying time and effective moisture diffusivity increased with the thickness of the onion puree.…”
Section: Introductionmentioning
confidence: 99%